Theology and psychology of submission: towards understanding the concept of Tawhid, unity and diversity - Abdullah, Fatimah (AMIN Research and Cultural Centre, 2011)
This article highlights the theological and psychological aspects of submission in Islam that distinguish it from concept of submission of different beliefs system. Submission is the cornerstone of any religious belief. To religiously submit is to surrender oneself to one's object of worship. Submission can be the result of fear of real or imagined authority and power or it may be the result of deep gratitude and love. Submission may be an internal subjective state of deep feelings and emotions or it may take the form of visible rites, rituals and offerings. Finally, submission may take different forms or grades. One may totally surrender oneself to the extent of complete abolition of mind and or he may simply treat his object with a mildfeeling of holiness and respect. Between these two extremes, there can exist a gradient or hierarchy of submissions and thus we can speak of different forms of submission: some of them extreme or irrational, and others that are acceptable and rationally defensible.